Clinical Recommendations on Emergency Medical Care Rendering to Children with Acute Intoxication - A. A. Baranov; S. F. Bagnenko; L. S. Namazova-Baranova; Y. S. Alexandrovich; K. V. Pshenisnov; E. A. Alexeyeva; L. R. Selimzyanova (Union of pediatricians of Russia, 2016)
The article is dedicated to the issue of intoxication in children. Acute accidental intoxication appears to be especially relevant for pediatric practice. Drugs, various chemicals frequently used in everyday life and in farming, as well as animal poisons, including snake poisons, may have a toxic effect on children. Specialists of professional associations of physicians "Russian Society of Emergency Medicine" and pediatricians "Union of Pediatricians of Russia" formulated and briefly described the main causes of acute intoxication in children, clinical manifestations and the most significant laboratory indicators of toxic manifestations for various substances, as well as therapy principles and algorithms for such conditions in compliance with principles of the evidence-based medicine. The article presents pathognomonic symptoms and peculiarities of drug intoxication, provides a description of mediator symptoms of intoxication with various substances, as well as the symptoms that may indicate toxic effect. The article contains a description of principles of correction of vital body functions, measures for removing toxic substances from the body and information on the main antidotes. Special attention is given to the most frequent types of intoxication (with organic acids, lye, naphazoline, paracetamol, snake poisons [viper bite]). The article lists stage of medical care rendering to children suffering from acute intoxication and presents prognosis and further management of pediatric patients suffering from such conditions.